Evaluating the change in central corneal thickness in neonates (term and preterm) in Indian population and the factors affecting it - Jethani, Jitendra (Indian J Ophthalmol, 2015)
BACKGROUND AND AIM: Central corneal thickness (CCT) of term and preterm infants in Indian population is not known. We did a prospective noninterventional study to measure the CCT in term and preterm infants. MATERIALS AND METHODS: An ultrasonic pachymeter was used. The data regarding the date of birth, expected date of delivery, birth weight were recorded. The preterm and the term infants were followed up at 8 weeks, 20 weeks and at 1-year. RESULTS: A total of 85 (170 eyes) children were included in the study. The mean age was 264.6 ± 21.8 days postconception. The mean birth weight and CCT were 1834.4 ± 512.1 g and 595.8 ± 72.4 μ respectively. A comparison of CCT on the basis postgestational age showed a mean thickness of 620.7 ± 88.8 and 574.4 ± 78.3 μ in the <260 days and >260 days age groups respectively. The difference was statistically significant (Student's test, P = 0.002). The CCT of preterm infants (<260 days) decreased from a mean value of 620.7 ± 88.8 μ to 534.1 ± 57.6 μ at the end of 1-year. CONCLUSION: We present the data of CCT in term and preterm infants in Indian population. We believe that the premature babies have slightly thicker corneas than mature term babies.